PENINGKATAN PERAN FORUM KEMITRAAN POLISI MASYARAKAT (FKPM) DALAM PENCEGAHAN TINDAK PIDANA - Andayani, Tri Wahyu (Fakultas Syariah, 2014)
The purpose of this paper is to improve role of police community partnership forum (FKPM) in the prevention of crime. Methodology approach in this study uses an empirical- juridical approach, because the scope of the research is to study law in action. A prevention effort of criminal act not only as police responsibility but also as society responsibility entirely. To develop a partnership between police and society, it is formed community policing model (Perpolisian Masyarakat/ Polmas) as regulated in Decree of Indonesia Chief Police No. Skep/737/X/2005 on Policies and Implementation Strategy of Community Policing Model in Police Duties. In other words, Indonesia police move or empowering the people (pemberdayaan masyarakat) in order to motivate the rising power of the people themselves for performing functions of the police. Idea of alternative police also can be called as an attempt for empowering the society to create security function in their surroundings.